Studi Komparasi Perihal Perumusan Tindak Pidana Kekerasan Terhadap Anak - Mufan Nurmi; Andi Najemi; Mohamad Rapik (Fakultas Hukum, Universitas Jambi, 2021)
The formulation of a crime is a way for every country in tackling crimes with a legal approach. Despite the similariteis of the child abuse and culture Indonesia and Malaysia might share, they also have different concepts regarding the formulation of criminal acts against children. Applying a comparative approach, this article explores the laws and regulations in the two countries and analyzes the regulatory concepts they provide. The objective is to look at the similarities and differences of each concept. The article demonstrates that the regulation of acts and sanctions in Indonesia and Malaysia has several similarities, such as the regulation regarding the age limit for children, as well as several differences, such as in the clarity of the formulation of offenses against children. The study of this matter is important, especially for Indonesia. The results of this comparative approach have allowed both countries, especially Indonesia, to borrow a number of important ideas regarding the formulation of violent crimes against children. Â ABSTRAK Perumusan tindak pidana merupakan cara setiap negara dalam menanggulangi kejahatan dengan pendekatan hukum. Sekalipun peristiwa kekerasan anak itu bisa sama dan dengan kultur yang serupa, Indonesia dan Malaysia bisa memiliki konsep yang berbeda mengenai perumusan tindak pidana kekerasan terhadap anak. Dengan melakukan pendekatan kompratif, artikel ini menelusuri peraturan perundang-undang di kedua negara itu serta menganalisis konsep-konsep pengaturan yang mereka berikan. Tujuannya adalah untuk melihat kelebihan dan kekurangan masing-masing konsep. Hasilnya, dalam artikel ini ditunjukkan bahwa pengaturan perbuatan dan sanksi di Indonesia dan di Malaysia memiliki beberapa persamaan seperti pengaturan mengenai batas usia anak, di samping juga memiliki beberapa perpedaan seperti dalam masalah kejelasan rumusan delik tindak kekerasan terhadap anak. Studi terhadap masalah ini menjadi penting, terutama bagi Indonesia. Hasil penelitian dengan pendekatan kompratif ini memungkinkan kedua negara, terutama Indonesia, meminjam sejumlah ide penting terkait perumusan tindak pidana kerasan terhadap anak.Â